The performance outcomes of dimensions of supply chain integration: a conceptual framework - Afshan, Nikhat (Business: Theory and Practice, 2013)
A systematic review of literature on the relationship between supply chain integration (SCI) and firm performance shows inconsistency in the results. Some of the studies show a direct relationship between SCI and firm performance, while other shows no significant relationship between these constructs. Further, there is a stream of research which proved that the relationship between SCI and performance is mediated through some intermediate performance outcomes. Based on the gaps identified through an extensive literature review, this study proposes that three dimensions of SCI- supplier integration, customer integration and internal integration will lead to different performance outcomes which will further influence financial performance of the firm. Further, a conceptual framework is presented postulating the relationship between  constructs of interest.